LIVER TRANSPLANTATION IN KRASNODAR: FIRST RESULTS - A.Y. Popov; A.N. Lischenko; M.N. Davydenko; A.A. Zavrazhnov; V.A. Porhanov (Вестник трансплантологии и искусственных органов)
Since April 2010 to December 2011 were performed 35 orthotopic transplantations of cadaveric whole liver. The indication for surgery was liver cirrhosis of different etiologies: 6 – autoimmune, 5 – primary biliary cirrhosis, 2 – toxic, 4 – unspecified, 18 – virus, two of which with the outcome in hepatocellular carcinoma. Caval anastomosis formed mainly «end-to-side». In five cases, to increase the arterial perfusion of the graft, we ligated the splenic artery. Surgical complications in the early postoperative period were seen in 4 patients (11.4%). In the late period we observed stricture of bile duct in 4 patients (11.4%). In their treatment we used various combinations of minimally invasive and open surgical procedures. 2 patients died (5.7%) – one of them on the sixth day because of intrahepatic portal vein thrombosis, another one in 6 months with a recurrence of autoimmune cirrhosis and humoral graft rejection.